Antiga Vila Boa de Goiás: experiências e memórias na/da Cidade Patrimônio - Gomide, Cristina Helou (2007)
This research points the patrimonial history of the City of Goiás, that was politician-administrative headquarters since the colonial period until the decade of 1930, when occurred the transference from the state capital of the former Vila Boa de Goiás to Goiânia - planned city for the new capital of the state of Goiás at that epoch. Investigating the history of this city, I perceived that the idea of the historic-patrimonial city was shaping itself while fortify the image of one city that appeared in local press divulgations as "root of the goiana culture". Since 1950, when the first actions of the SPHAN in the City of Goiás had occurred, I concentrate my reflections into the politics of buildings inventorying that were considered patrimonial, and I begun to scan inside the former Vila Boa de Goiás, the trajectory of the responsible agency for the preservation of historical, artistic and cultural things in Brazil. Based upon this investigation, I realized some landmarks in this process. In 1978 IPHAN promoted another falling inventorying in the city, extending the patrimony notion and considering important real urban webs. From 1997 to 1999, dialoguing with inhabitants who had remained in the Cidade de Goiás even after the transference of the capital for Goiânia, I noticed that the history of the transference of the capital brought to them discomfort and hurt, while these people alluded, many times to the image of the city that was abandoned after that change. Until that moment, the "marasmus" of the city - one of the factors pointed to justify the change of the capital - appeared as something negative, although the urban space leaded into the notion of historical patrimony and those inhabitants worried themselves to defend the space wich they lived in. From 2003 the 2005, worried to understand the way as the inhabitants of the historical city saw and lived this city, I treated to look for people who live in less supplied quarters of former Vila Boa. In that period, more engaged to the city as a patrimonical place and more vinculated to the touristic practical that envolved the city, some inhabitants intercrossed themselves to the local touristic movement, although they still felt detached, in many cases, from the dynamic of the so called city historical center. In 2007 february I was with a new way of looking and thinking about that subject, when I tried to dialogue with people who work and live the daily dynamics of the historical center of Goiás. I talked with confectioner, artisans, managers and workers of shops located there. I realized a notable transformation in the ways that people see and live this city. The "marasmus" before told as part of the hurt from the transference of the capital, today had changed into a significative form of "tranquillity", expressing itself, to them, as quality of life. Intercrossed at the construction history of a hegemonicly memory built of the local patrimony, these habitants re-signify the traditions doing part of the memory like a part of its lives. At last, analysing especially touristic and propagandistic folders (destined to the trajectory of the city visitor), postcards, newspapers articles, literary and verbal narratives, I appoint in this thesis the experiences and the memories expressions in and of the Patrimonial City succeeding to perceive the way how inhabitants live and mean that city